2018
DOI: 10.1002/adma.201801372
|View full text |Cite
|
Sign up to set email alerts
|

A Wide‐Range Photosensitive Weyl Semimetal Single Crystal—TaAs

Abstract: Mid- and even long-infrared photodetection is highly desired for various modern optoelectronic devices, and photodetectors that operate at room temperature (RT) remain challenging and are being extensively sought. Recently, the Weyl semimetal has attracted much interest, and its Lorentz invariance can be broken to have tilted chiral Weyl cones around the Fermi level, which indicates that the photocurrent can be generated by the incident photons at arbitrarily long wavelengths. Furthermore, the atypical linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 50 publications
4
65
0
Order By: Relevance
“…[ 37 ] In addition, the detectivity is determined as high as 4.0 × 10 10 Jones at 520 nm with an effective power 0.45 nW, which is far better than those of the previously reported photodetectors based on 2D materials, such as SnSe (≈10 7 Jones), [ 38 ] MoTe 2 (≈10 8 Jones), [ 37 ] and TaAs (≈10 8 Jones). [ 39 ] As present in Figure S9 in the Supporting Information, the gain reaches a maximum value of 3453% at 520 nm with an effective power 0.45 nW. The related performance parameters are finally compared with those of the previously reported 2D photodetectors ( Table 1 ).…”
Section: Figurementioning
confidence: 95%
“…[ 37 ] In addition, the detectivity is determined as high as 4.0 × 10 10 Jones at 520 nm with an effective power 0.45 nW, which is far better than those of the previously reported photodetectors based on 2D materials, such as SnSe (≈10 7 Jones), [ 38 ] MoTe 2 (≈10 8 Jones), [ 37 ] and TaAs (≈10 8 Jones). [ 39 ] As present in Figure S9 in the Supporting Information, the gain reaches a maximum value of 3453% at 520 nm with an effective power 0.45 nW. The related performance parameters are finally compared with those of the previously reported 2D photodetectors ( Table 1 ).…”
Section: Figurementioning
confidence: 95%
“…One of the main factors that hinders the development of photonics and optoelectronics is the lack of materials with broad‐band optical response and strong light–matter interaction. Therefore, it is an urgent need and many efforts have been devoted to searching for this kind of novel materials …”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, topological insulator and Dirac semi‐metal material have risen a great interest in quantum physics research . These emerging materials have remarkable potential for LIR detection due to its distinct electronic structure . Such novel materials also need to combine with other materials to promote entire performance .…”
Section: Recent Design Strategies For 2d‐based Photodetectorsmentioning
confidence: 99%
“…[90][91][92][93][94] These emerging materials have remarkable potential for LIR detection due to its distinct electronic structure. [95][96][97] Such novel materials also need to combine with other materials to promote entire performance. 39,73,98,99 Qiao et al incorporated a similar hexagonal symmetry Bi 2 Te 3 with graphene as shown in Figure 5G, the photodetector demonstrated a strong and broadband responsivity reach telecommunication band (35 A/W and extend to 1550 nm depicted in Figure 5H).…”
Section: Single Layer Enhanced Photoconductorsmentioning
confidence: 99%